Applying Geoaccumulation Index and Enrichment Factor for Assessing Metal Contamination in the Sediments of Euphrates River, Iraq - Kamel, Laith Hemed; Mahmood, Mahmood B.; Al-zurfi, Sadiq K. (Iraqi Journal of Science, 2023)
The current study looked into heavy metal poisoning of the Euphrates river which runs from Al-Kifl to Kufa in Iraq. One of the goals of this research was to determine the pollution levels and the contamination sources. We looked at six heavy metal (Cd, Pb, Zn, Cr, Fe, and Mn) characteristics in sediment, taking samples from six sites along the Euphrates every season from March 2020 to January 2021. To assess pollution levels, three indices were chosen: enrichment factor (EF), geo-accumulation index (I-geo) and contamination factor (CF). According to EF, the Cd and Pb elements recorded considerable enrichment, very high enrichment and extremely high pollution at practically all sites in four seasons, while the remainder of the HMs recorded deficiency to minimal enrichment and moderate enrichment. In all seasons, the geo-accumulation index showed significant contamination with Cr and moderate to low contamination with other metals. Except Cr in spring, which was recorded with moderate contamination, significant contamination and very high contamination, the CF values of all metals in all sites indicated no sediment contamination by these elements.